2007
DOI: 10.1080/13607860701365972
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban differences in the effects on mental well-being of caring for people with stroke or dementia

Abstract: 2 Rural-urban differences in the effects on mental well-being of caring for people with stroke or dementia.Rural and urban differences in the effects of care-giving are not well documented. 3 Rural-urban differences in the effects on mental well-being of caring for people with stroke or dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…Sardinian nurses should sensitize politicians to provide more resources for caregivers. It has been shown that rural caregivers have worse QOL and fewer services than urban caregivers (Tommis et al, 2007) and could benefit from supportive programs (S. A. Smith & Bell, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sardinian nurses should sensitize politicians to provide more resources for caregivers. It has been shown that rural caregivers have worse QOL and fewer services than urban caregivers (Tommis et al, 2007) and could benefit from supportive programs (S. A. Smith & Bell, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…No studies have investigated the meaning of QOL for Sardinian AD caregivers. Although some international studies have shown that AD caregivers living in rural areas have worse QOL and use fewer formal services than those living in urban areas (Morgan, Semchuk, Stewart, & D'Arcy, 2002;Tommis et al, 2007), no researchers have specifically explored the meaning of QOL for rural AD caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…In Saskatchewan, these differences are accelerated by the loss of formal health care services in the more rural areas of Saskatchewan (Jaffe & Blakley, 1999). If the type and amount of support services are predictive of caregiver mental well-being (e.g., Tommis et al, 2007), it is surprising then that the caregivers of people with dementia in the current study were able to cope similar to their more urban counterparts.…”
Section: Discussionmentioning
confidence: 81%
“…The presumed mechanism of differences in urban/rural coping is reduced accessibility to supports for rural caregivers, which influences coping strategies, which, in turn, results in differential burden and distress for underserviced caregivers. Tommis et al (2007) found that male caregivers residing in rural locations had lower psychological wellbeing, whereas female caregivers scored the same on psychological well-being regardless of location. Bien and colleagues' (2007) findings supported this hypothesized difference in caregiver outcomes; they found that rural caregivers reported more burden than urban caregivers.…”
Section: Caregivers' Reports Of Burden and Distressmentioning
confidence: 89%
“…In one report, researchers note that rural caregivers provide almost 50 hr of care a week (Kosberg, Kaufman, Burgio, Leeper, & Sun, 2007). Interestingly, gender differences appear in comparisons of urban and rural caregivers; male caregivers in rural environments exhibit poorer mental health as compared with their urban-dwelling counterparts; however, no differences emerge between female caregivers in the two locations (Tommis et al, 2007). Home care staff note that rural caregivers may be reluctant to use services in the area and may not request help until a crisis situation emerges (Morgan et al, 2002).…”
Section: Articlementioning
confidence: 99%